All-in-One High-Power-Density Vibrational Energy Harvester with Impact-Induced Frequency Broadening Mechanisms - Yongqi Cao (Micromachines, 2021)
This paper proposes an electrostatic-piezoelectric-electromagnetic hybrid vibrational power generator with different frequency broadening schemes. Both the nonlinear frequency broadening mechanisms and the synergized effect of the electrostatic-piezoelectric-electromagnetic hybrid structures are investigated. The structure and performance of the composite generator are optimized to improve the response bandwidth and performance. We propose that the electrostatic power generation module and the electromagnetic power generation module be introduced into the cantilever beam to make the multifunctional cantilever beam, realizing small integrated output loss, high output voltage, and high current characteristics. When the external load of the electrostatic power generation module is 10 kΩ, its peak power can reach 3.6 mW; when the external load of the piezoelectric power generation module is 2 kΩ, its peak power is 2.2 mW; and when the external load of the electromagnetic power generation module is 170 Ω, its peak power is 0.735 mW. This means that under the same space utilization, the performance is improved by 90%. Moreover, an energy management circuit (ECM) at the rear end of the device is added, through the energy conditioning circuit, the device can directly export a 3.3 V DC voltage to supply power to most of the sensing equipment. In this paper, the hybrid generator’s structure and performance are optimized, and the response bandwidth and performance are improved. In general, the primary advantages of the device in this paper are its larger bandwidth and enhanced performance.